SANKSI HUKUM TERHADAP PELANGGARAN PENGGUNAAN TENAGA KERJA ASING PASCA UU CIPTA KERJA - Christina NM Tobing (SOL JUSTICIA, 2022)
Indeed, the Indonesian state prioritizes the placement of domestic workers over foreign workers in accordance with the mandate of the Constitution Article 27 paragraph (2). In fact, the existence of foreign workers is still needed related to investment in various sectors that require special technology and expertise that have not been fulfilled by Indonesian workers. The problem is, foreign workers enter sectors that do not require special skills, even though many unskilled workers are unemployed. The Job Creation Law cuts down the licensing process for the use of foreign workers and removes some criminal sanctions and/or replaces them with administrative sanctions for violations of the norms for the use of foreign workers. The purpose of this paper is to describe the legislative ratio of changes in legal sanctions for the use of foreign workers in Indonesia after the Job Creation Act. This research is normative legal research, with a statutory approach and a conceptual approach. The stages of the research were carried out by examining the laws and regulations, namely the Employment Creation Act for the labour cluster and the Manpower Act as well as the implementing regulations related to foreign workers, then analysed provisions of legal sanctions and drawn conclusions. The results of the study, the Job Creation Law revoked the imprisonment and fines for employers who did not have an IMTA, by removing Article 42 paragraph (1) of the Manpower Law, previously a criminal offense in accordance with Article 185 paragraph (1). After the Employment Creation Law, it is sufficient for employers to only have RPTKA Ratification, and violators are subject to administrative sanctions in the form of fines, even though the function of IMTA is the same as RPTKA. The Job Creation Law abolishes criminal sanctions for violations of Article 44 paragraph (1) concerning positions and standards of competence (expertise), replacing them with administrative sanctions in the form of revocation of RPTKA Ratification. The ratio legis the elimination of criminal sanctions and/or replacing them with administrative sanctions in the Manpower Act by the Job Creation Act shows a decrease in the protection of the constitutional rights of Indonesian workers to work opportunities and decent income for humanity and is more pro-investment.